ABORDAGEM STEAM: UMA PROPOSTA DE ENSINO E DE APRENDIZAGEM PARA ALUNOS DO ENSINO MÉDIO DE UMA ESCOLA DO CAMPO - Prates, Johnattan Bordinhão (2023)
The present research aims to investigate the contributions of the STEAM Approach to the teaching and learning process of high school students in a rural school. The activities developed according to this approach allow students to solve problems through collaborative work, with the student actively participating in the construction of their knowledge. The participants in this research are high school students from João Octávio Nogueira Leiria Rural School located in the municipality of São Francisco de Assis in the state of Rio Grande do Sul. First, an analysis of STEAM projects in the Integrative Mathematics Projects textbooks for high school, offered to Brazilian schools by the National Textbook Program - PNLD, was conducted. Then, a literature review was conducted on the STEAM approach and Mathematics. Based on questioning the students, who were participants in the research, about their topics of interest, the development of a project centered around the theme of water, following the STEAM approach, was proposed. The researcher used a field diary as a data collection instrument, a semi-structured questionnaire applied to the students, and data obtained from the project implementation. We concluded that the construction of the STEAM project provided the research participants with greater autonomy, the development of critical thinking, self-esteem, knowledge and the use of technology, as well as the formulation of conjectures to solve problems. Furthermore, we also concluded that the research fostered relationships and interactions with various areas of knowledge, facilitating connections between the fields of science, technology, engineering, arts, and mathematics related to water-related topics.